Germany from the outside rethinking German cultural history in an age of displacement - Johnson, Laurie 1966- (New directions in German studies, 2022)
"Illuminates our understanding of the nation and the role of culture in the nation, in an era of extreme displacement and increased migration, in "German" geopolitical and linguistic-cultural spaces